THE CONCEPT OF POLITICAL CRIMES IN LITHUANIA, 1919–1940 - Černevičiūtė, Sigita (Teisė, 2016)
The article analyzes phenomena of political crimes in Lithuania 1919–1940. It reveals the concept of political crimes through the criminal law of the First Republic of Lithuania. Three distinct groups of political crimes are examined – rebellion, high treason and subversion.